Analisis Kemampuan Pemecahan Masalah Aritmatika Sosial Ditinjau dari Gaya Kognitif Impulsif dan Reflektif Siswa MTs - Nurlailis Kurniawati; Sudi Prayitno; Laila Hayati; sri Subarinah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the ability to solve social arithmetic problems in terms of impulsive and reflective cognitive styles. This type of research is descriptive qualitative. The research subjects were class VIII MTs Al-Khairiah NW Rajek in the 2020/2021 school year. Data collection techniques using tests and interviews. The test in question is a cognitive style test using the Matching Familiar Figure Test (MFFT), and a problem-solving ability test. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study indicate that students' mathematical problem solving abilities with impulsive cognitive style require less time to answer questions. Impulsive cognitive style students at the stage of understanding the problem, many students do not understand the questions well, at the stage of making plans, implementing plans, and at the stage of looking back students have not been able to solve problems well, students are still careless in determining formulas, not careful in counting, rushing rush in solving questions, do not re-check the answers. The mathematical problem solving ability of students with reflective cognitive style takes a long time to answer questions. Students with reflective cognitive style at the stage of understanding the problem, making plans have been able to solve the problem well, at the stage of implementing the plan some students are still wrong in counting, while at the stage of looking back reflective students do not check back on the answer sheet.